Binary hypotheses for bipolar mass loss in transients - Fitzpatrick, BJR (2012)
We investigate binary hypotheses for the formation of bipolar nebulae using the smoothed particle hydrodynamics code Gadget-2. In the general case, we present a parameter study of mass loss from very simple common envelope models, which seems to show a strongly bipolar trend for sufficiently oblate envelopes and low enough spiral-in injection energy. The density profiles of the envelopes produce differing structure within the ejecta. We also investigate 3 specific bipolar mass loss events. In the case of the outer nebula of SN 1987A, we study the effects of fast polar jets interacting with a pre- existing progenitor wind and find that these are consistent with the observed light echoes from the nebula, in particular for the feature known as ’Napoleon’s Hat’. In the case of Cas A, we briefly study the effects of close binarity on supernova ejecta and suggest the influence of a close, compact companion may lead to at least one jet-like disturbance that may be observable in a supernova remnant. Finally, we study whether a fast bipolar wind, similar to that of Eta Car’s present wind, may inflate ejecta similar to that produced in the common envelope models to a shape consistent with that of Eta Car’s Homunculus Nebula.